2014
DOI: 10.1371/journal.pone.0086111
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiological Implications of Mucin (MUC) Expression in the Outcome of Small Bowel Cancer

Abstract: Mucins have been associated with survival in various cancer patients, but there have been no studies of mucins in small bowel carcinoma (SBC). In this study, we investigated the relationships between mucin expression and clinicopathologic factors in 60 SBC cases, in which expression profiles of MUC1, MUC2, MUC3, MUC4, MUC5AC, MUC6 and MUC16 in cancer and normal tissues were examined by immunohistochemistry. MUC1, MUC5AC and MUC16 expression was increased in SBC lesions compared to the normal epithelium, and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
4
17
0
Order By: Relevance
“…Sections were incubated with a primary antibody (DF3 diluted 1∶50, 37°C, 32 min; Ccp58 diluted 1∶200, 37°C, 24 min; 8G7 diluted 1∶3000, 37 °C, 32 min; CLH2 diluted 1∶100, 37°C, 24 min; CLH5 diluted 1∶100, 37°C, 24 min; OC125 diluted 1: 100, 37°C, 24 min; anti-human MUC17 diluted 1: 100) in phosphate-buffered saline (PBS) pH 7.4 with 1% bovine serum albumin, and stained on a Benchmark XT automated slide stainer using a diaminobenzidine detection kit (ultraView DAB, Ventana Medical Systems). For MUC3 staining, sections were treated at 100°C for 10 min in 0.01 M citrate buffer at pH 6.0, and then reduced with 0.01 M dithiothreitol in 0.1 M Tris/HCl buffer (pH 8.0) for 30 min at room temperature and alkylated with 0.025 M iodoacetamide in 0.1 M Tris/HCl buffer (pH 8.0) for 30 min [13] , [17] , [27] . They were incubated with mMUC3-1 at 4°C for 16 h and stained by avidin-biotin complex method.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sections were incubated with a primary antibody (DF3 diluted 1∶50, 37°C, 32 min; Ccp58 diluted 1∶200, 37°C, 24 min; 8G7 diluted 1∶3000, 37 °C, 32 min; CLH2 diluted 1∶100, 37°C, 24 min; CLH5 diluted 1∶100, 37°C, 24 min; OC125 diluted 1: 100, 37°C, 24 min; anti-human MUC17 diluted 1: 100) in phosphate-buffered saline (PBS) pH 7.4 with 1% bovine serum albumin, and stained on a Benchmark XT automated slide stainer using a diaminobenzidine detection kit (ultraView DAB, Ventana Medical Systems). For MUC3 staining, sections were treated at 100°C for 10 min in 0.01 M citrate buffer at pH 6.0, and then reduced with 0.01 M dithiothreitol in 0.1 M Tris/HCl buffer (pH 8.0) for 30 min at room temperature and alkylated with 0.025 M iodoacetamide in 0.1 M Tris/HCl buffer (pH 8.0) for 30 min [13] , [17] , [27] . They were incubated with mMUC3-1 at 4°C for 16 h and stained by avidin-biotin complex method.…”
Section: Methodsmentioning
confidence: 99%
“…Carcinoma cells are considered to be stained positively when at least one of the components was positive. A tumor was considered positive if more than 5% of carcinoma cells were stained, based on our previous use of 5% as the cutoff for mucin expression [17] , [28] – [33] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ESD guidelines were previously based on hematoxylin and eosin staining; however, numerous studies have reported that the expression of cell adhesion molecules, cell surface molecules, membrane-associated mucin phenotypes and collagen phenotypes are associated with lymph node metastasis and prognosis of carcinomas in multiple organs (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Mucin 1, cell surface associated (MUC1) is a transmembrane member of the mucin family and has been reported to be associated with metastatic progression (16).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The study of mucin expression patterns and its regulation becomes a potential strategy in finding cancer biomarkers. [4][5][6][7][8][9] Figure 1 -Tumors use mucins for invasion, metastasis and protection. a.Tumors use the antiadhesive effect of mucins to detach from the tumor mass and surrounding stroma and invade.…”
Section: Aims and Motivationmentioning
confidence: 99%